(untitled) (Journal of Civil Engineering Researchers, 2022)
In recent years, studies have been started for the use of light-grained concrete in conventional reinforced concrete structures, it is expected that the use of light-grained concrete without having a negative effect on the use of the structure will reduce the costs in construction and reduce the structural mass. As a result, the earthquake load will be reduced. In this research, concrete with an approximate compressive strength of 18.24 megapascals and an approximate specific weight of 1800 kg/m3 was obtained by using Lika grain style. In order to evaluate the structural behavior of lightweight concrete, 5 concrete columns were built in the laboratory and were subjected to axial load and the results related to these columns were presented, and then a suitable model for these columns was presented by Abaqus finite element software and analytical studies It was done on the relevant results, which are in good agreement with the laboratory results. The agreement of the results obtained from the modeling with the laboratory results is a proof of the accuracy of the built model. © 2017 Journals-Researchers. All rights reserved